Diagnostics Of Pedagogical Staff Readiness For Teaching Natural Sciences In English - Elena Burdina, Aiman Nurzhumbayeva,; Kozhayeva, Sanim; Leonid Bulyga, Zhanna Temerbayeva, (Opción, 2019)
This article analyzes the formation of pedagogical staff readiness for teaching natural sciences in English within the frame of updated content of education. The theoretical and empirical research is conducted to examine the readiness of the working at school and using new technologies pedagogues for teaching in English. The results of research allow improving the pedagogical process at the secondary school as a contemporary educational system uses English language in teaching natural sciences. In conclusion, the development of a technique begins with the theoretical analysis of the readiness essence of pedagogical staff for teaching natural sciences in English